Forbidden Science 4: The Spring Hill Chronicles. The Journals of Jacques Vallee, 1990-1999 by Jacques Vallee - Alexander, John B. (Journal of Scientific Exploration, 2019)
As Jacques Vallee is an inveterate scribe, Forbidden Science 4: The Spring Hills Chronicles is an excellent compendium of contemporaneous notes for the period between January 1990 and December 1999. While there is a customary focus on the business at hand, UFOs, he also includes a wide variety of personal information such as his health, emotional state, cinema exploits, tips on restaurants, and books that he and his wife, Janine, have read. The weather, especially if cold, also draws commentary. Importantly, the role Janine played in Jacques’ life cannot be overstated and she permeates the text; her guidance, counsel and companionship vital to the exploration. Occasionally poems are included and there are infrequent comments on the Dow Jones Industrial Averages. He reminds us that it was in December, 1999 that the 10,000 mark was broken for the first time. Things have changed. Also of interest may be the running narrative of the rapidly changing geopolitical circumstances that exert influence on all topics being considered. Conditions in France and America predominate, but emerging circumstances in many other countries are given consideration. That the Soviets may have been concerned about a real extraterrestrial threat is learned early in the book. Many other surprising revelations soon follow. Hardly a topic on anomalies is missed from remote viewing and abductions by ET (and maybe the military) to fastwalkers and cattle mutilations. There is a dazzling array of contacts Jacques has made over the year and very few of the extensive list of characters involved in such research are missing. A treasure trove of information about researchers, either he personally knows them, or has heard about them. One has but to explore the 43 pages of the index to conclude that he has extensive experience in several fields. Likely (if you’re similar to me) you will not run through the book very quickly. I found it necessary to have my computer handy and engage in frequent Google searches on all manner of topics. As an example, he mentions being in the woods at a meeting of “witches and warlocks” and singing The Blood of the Ancients. Damned if I didn’t find the song available and sung on the Internet.